The Correlation Between Serum Vitamin D Level and Total Antioxidant Capacity in diabetic and Non-diabetic Subjects in Iran - Ali Zare-Mirzaie; Behrang Kazeminezhad; Mona Akbari Ghouchani (Iranian Society of Pathology, 2018)
Background& Objective:  Increase in intra- and extracellular glucose levels can cause oxidative stress, and the prolonged imbalance between prooxidants and antioxidantscan lead to cell damage and the associated complications in patients with diabetes. Vitamin D acts as a strong antioxidant in the body and several studies emphasized on its important role to prevent oxidative stress in prediabetic and diabetic subjects. The current study aimed at determining and comparing the total antioxidant capacity (TAC) in individuals with hemoglobin A1c (HbA1c) below and above 6.5%, and its correlation with vitamin D levels. Methods: The current cross sectional study was conducted on a total of 107 patients with diabetes (HbA1c >6.5%) and 107 non-diabetic subjects (HbA1c <6.5%) referred to Rassool Akram Hospital, Tehran, Iran from 2015 to 2016, as the sample population. The two groups were compared regarding their TAC and vitamin D serum levels and the association between vitamin D concentration and TAC was evaluated.  Results: Age and body mass index (BMI)were significantly higher in patients with diabetes, compared with the serum levels of vitamin D and TAC (P P=0.003). In multivariate regression model, the duration of diabetes was also significantly associated with TAC level (beta coefficient=-0.82, P <0.001).  Conclusion: The low serum levels of TAC and vitamin D in patients with diabetes could be indicative of oxidative stress in the presence of high blood glucose levels. Supplementation of vitamin D in patients with diabetes might be effective to control the negative impacts of the disease and decrease cells' exposure to oxidative environment in prediabetes.